MiR‐148a controls metabolic programming and survival of mature CD19‐negative plasma cells in mice. Issue 5 (1st February 2021) - Pracht, Katharina; Meinzinger, Julia; Schulz, Sebastian R.; Daum, Patrick; Côrte‐Real, Joana; Hauke, Manuela; Roth, Edith; Kindermann, Dorothea; Mielenz, Dirk; Schuh, Wolfgang; Wittmann, Jürgen; Jäck, Hans‐Martin
Abstract: Long‐lived antibody‐secreting plasma cells are essential to establish humoral memory against pathogens. While a regulatory transcription factor network has been established in plasma cell differentiation, the regulatory role of miRNAs remains enigmatic. We have recently identified miR‐148a as the most abundant miRNA in primary mouse and human plasma cells. To determine whether this plasma cell signature miRNA controls the in vivo development of B cells into long‐lived plasma cells, we established mice with genomic, conditional, and inducible deletions of miR‐148a. The analysis of miR‐148a‐deficient mice revealed reduced serum Ig, decreased numbers of newly formed plasmablasts and reduced CD19‐negative, CD93‐positive long‐lived plasma cells. Transcriptome and metabolic analysis revealed an impaired glucose uptake, a reduced oxidative phosphorylation‐based energy metabolism, and an altered abundance of homing receptors CXCR3 (increase) and CXCR4 (reduction) in miR‐148a‐deficient plasma cells. These findings support the role of miR‐148a as a positive regulator of the maintenance of long‐lived plasma cells. Abstract : miR‐148a favors differentiation and maintenance of long‐lived plasma cells by regulating the surface abundance of homing receptors and cellular metabolism via Glut‐1‐mediated glucose uptake and oxidative phosphorylation. Therefore, this single microRNA can act as a positive regulator of the maintenance of long‐lived plasma cells.